Evaluation of anesthesia effects on [ 18F]FDG uptake in mouse brain and heart using small animal PET - Toyama, Hiroshi; Ichise, Masanori; Liow, Jeih-San; Vines, Douglass C.; Seneca, Nicholas M.; Modell, Kendra J.; Seidel, Jurgen; Green, Michael V.; Innis, Robert B. (Nuclear medicine and biology, 2004)
This study evaluates effects of anesthesia on 18F-FDG (FDG) uptake in mouse brain and heart to establish the basic conditions of small animal PET imaging. Prior to FDG injection, 12 mice were anesthetized with isoflurane gas; 11 mice were anesthetized with an intraperitoneal injection of a ketamine/xylazine mixture; and 11 mice were awake. In isoflurane and ketamine/xylazine conditions, FDG brain uptake (%ID/g) was significantly lower than in controls. Conversely, in the isoflurane condition, %ID/g in heart was significantly higher than in controls, whereas heart uptake in ketamine/xylazine mice was significantly lower. Results suggest that anesthesia impedes FDG uptake in mouse brain and affects FDG uptake in heart; however, the effects in the brain and heart differ depending on the type of anesthesia used.